The effects of yoga on dyspnea, sleep and fatigue in chronic respiratory diseases - Ozer, Zulfunaz; Turan, Gulcan Bahcecioglu; Aksoy, Meyreme (Elsevier Sci Ltd, 2021)
Purpose: This study was carried out to find out the effects of yoga applied to chronic respiratory disease patients on dyspnea, sleep quality and fatigue. Material and method: The study was conducted between May and August 2020 as a randomized controlled study. 'Personal Information Form', 'Respiratory Functions Monitoring Form', 'COPD and Asthma Fatigue Scale (CAFS), Asthma and COPD Sleep Impact Scale (CASIS) and Modified Medical Research Council Dyspnea Scale (mMRC) were used in data collection. Results: When the post-test mean scores of the patients in the experimental and control group were compared, it was found that CAFS, CASIS and mMRC mean scores of the patients in the experimental group decreased positively compared to the patients in the control group and the difference between was found to be statistically significant (p < 0.05). Conclusion: Yoga has been found to reduce the severity of dyspnea and fatigue and improve sleep quality in chronic respiratory diseases.
Keywords: Chronic respiratory diseases; Nursing; Yoga